5(3y+3)-4=1

Simple and best practice solution for 5(3y+3)-4=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3y+3)-4=1 equation:


Simplifying
5(3y + 3) + -4 = 1

Reorder the terms:
5(3 + 3y) + -4 = 1
(3 * 5 + 3y * 5) + -4 = 1
(15 + 15y) + -4 = 1

Reorder the terms:
15 + -4 + 15y = 1

Combine like terms: 15 + -4 = 11
11 + 15y = 1

Solving
11 + 15y = 1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 15y = 1 + -11

Combine like terms: 11 + -11 = 0
0 + 15y = 1 + -11
15y = 1 + -11

Combine like terms: 1 + -11 = -10
15y = -10

Divide each side by '15'.
y = -0.6666666667

Simplifying
y = -0.6666666667

See similar equations:

| 4z+5/4=5z-4/5 | | 3-7x=5x-57 | | 3(3t+6)=24 | | -12.13=2.42y+0.6y-13.64 | | 12n-10=4n+6 | | -3r-18=-14-7r | | 3y-19=14+2y | | 12w-9-10w=11 | | 1.7x=7x | | 9+n=-9+3h | | 1/7(v+1/4)=2(3v/2-5/2) | | c=60+18 | | 9+6x=x+72 | | 54+5x+4x=180 | | 4y+15=6y/1 | | 11+7y-2=39-13y | | -2(-4u+3)=8u-11 | | -5(x+2)-43=1-29 | | 2/7(t+2/3)=1/5(t-2/3) | | 1/2=(3-2m)/(4m-6) | | 33=y+3-0.4y | | A=a+(n-8)d | | .5(x+5)+.10*x=5.65 | | -4-3x+x^2=0 | | 3(w+8)=9w+42 | | -n=20 | | X+34=4x | | 20-2x=3.3 | | -3x+36=-9(x+2) | | X^2+2x^2=15x | | 2(x+2)=-9x+15 | | 3x=(x+64) |

Equations solver categories